The influence of the parental child-rearing gender-role attitude on children’s social adjustment in single- and two-parent families: the mediating role of intergenerational identity - I-Jun Chen; Yiyue Wang; Zhiyin Sun; Yunping Song; Liling Wang; Mengping Yang (Humanities & Social Sciences Communications, 2023)
Abstract Family is an important system that influences children’s social adjustment. Parents are an important member of the family system, and their parental child-rearing gender-role attitudes (PCGA) will have a significant impact on their children’s social adjustment. This study used a sampling method to compare the intergenerational differences between family members’ PCGA, identity with parents and social adjustment in single- and two-parent families through 931 single-parent families and 3732 two-parent families in Suzhou, China. The study explored the mediating role of children’s identity with parents on parents’ PCGA and children’s social adjustment in different family structures. The results showed that: (1) parents’ masculinity rearing, femininity rearing of PCGA and children’s social adjustment in two-parent families were significantly higher than those in single-parent families; (2) children’s identity with parents mediated the relationship between femininity rearing of parents’ PCGA and children’s social adjustment; (3) the mediated model of children’s identity with parents was found to be significantly different between single-parent and two-parent families.